2010
DOI: 10.1007/s00425-010-1183-0
|View full text |Cite
|
Sign up to set email alerts
|

Whirly1 in chloroplasts associates with intron containing RNAs and rarely co-localizes with nucleoids

Abstract: The nucleic acid binding protein Whirly1 of barley has been located to both chloroplasts and the nucleus of the same cell. Immunogold labelling furthermore showed that in vivo Whirly1 does not strictly co-localize with DNA in chloroplasts, while it is closely associated with DNA in the nucleus. High-resolution imaging of Whirly1-GFP and PEND-RFP fusion proteins revealed that only a minor part of Whirly1 co-localizes with nucleoids. The co-localization with nucleoids is in accordance with the detection of Whirl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 38 publications
7
88
1
2
Order By: Relevance
“…In fact, sizes and positions of different nucleoid sub-populations could very well reflect the different requirements for enzymatic activities within the plastid nucleoids during plastid biogenesis. First support for this comes from co-localization studies of different plastid nucleoid-associated proteins (ptNAPs) (Melonek et al 2010). …”
Section: Dynamics In the Organization Of The Multicopy Chloroplast Gementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, sizes and positions of different nucleoid sub-populations could very well reflect the different requirements for enzymatic activities within the plastid nucleoids during plastid biogenesis. First support for this comes from co-localization studies of different plastid nucleoid-associated proteins (ptNAPs) (Melonek et al 2010). …”
Section: Dynamics In the Organization Of The Multicopy Chloroplast Gementioning
confidence: 99%
“…Another protein possibly involved in anchoring of plastid nucleoids to thylakoid membranes is the tetratricopeptide-containing chloroplast protein of 34 kDa (TCP34), which was shown to stably associate with thylakoid membranes (Weber et al 2006). Immunological analysis revealed that the protein is a TAC component (Weber et al 2006;Melonek et al 2010). The recombinant TCP34 protein showed specific binding to chloroplast DNA isolated from spinach (Weber et al 2006).…”
Section: Mfp1 Tcp34 and Ptac16mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was proposed that plastidic WHY1 in maize (Zea mays) and barley both have functions in RNA processing and that the plastidic WHY proteins in Arabidopsis have a function as antirecombination proteins that could be involved in maintaining plastome DNA stability (Maréchal et al, 2008(Maréchal et al, , 2009Prikryl et al, 2008;Cappadocia et al, 2010;Maréchal and Brisson, 2010;Melonek et al, 2010).…”
mentioning
confidence: 99%
“…Here, we propose that WHIRLY1 is involved in the perception of redox changes in the photosynthetic apparatus and in an SA-dependent transduction of this information to the nucleus. Biochemical studies have shown that chloroplast WHIRLY1 is present in nucleoid fractions [65,66]. Moreover, immunogold-labelling studies have shown that WHIRLY1 is closely associated with thylakoid membranes [59], as shown in figure 3.…”
Section: The Whirly Family Of Proteinsmentioning
confidence: 93%